Characterization of Monoclonal Antibodies to Human Tissue-Type Plasminogen Activator: Catalytic Inhibition and One-Two Chain Discriminatory Reactivities - Stigbrand, Torgny; Frängsmyr, Lars; Bergsdorf, Nils; Wallen, Per (Thrombosis and Haemostasis, 1989)
A new set of monoclonal antibodies was generated against the tissue plasminogen activator (t-PA). One of the antibodies, 1:3 C5, was found to be able to distinguish between the one- and two-chain form of t-PA and also exerted significant amidolytic inhibitory activity. Several of the antibodies, as judged from their binding properties in immunosorbent tests, were found to be suitable for immunoaffinity purification purposes, i.e. 1:3C5, 1:3 G5, and 1:2 B9. Three of the mabs, 1:2 B9, 1:3 G5 and 2:2 BIO, were selectively reactive with the A-chain of t-PA, whereas indirect evidences indicated 1:3 C5 to be reactive with a conformational epitope on the B-chain. Three of the antibodies were reactive with porcine t-PA. This new set of antibodies should prove useful for structure-function investigations of t-PA.
Keywords: Tissue plasminogen activator; Fibrinolysis; Monoclonal antibodies